1993
DOI: 10.1128/jcm.31.3.706-707.1993
|View full text |Cite
|
Sign up to set email alerts
|

Production of enterotoxins and toxic shock syndrome toxin by bovine mammary isolates of Staphylococcus aureus

Abstract: The production of staphylococcal enterotoxin A (SEA), SEB, SEC, SED, and SEE and toxic shock syndrome toxin 1 by bovine mammary isolates of Staphylococcus aureus was evaluated. Enterotoxin secretion was detected by immunodiffusion using specific polyclonal antisera. Of 262 isolates examined, 75 (28.6%) produced one or more toxins. The most common pattern was secretion of both SEC and SED and toxic shock syndrome toxin 1. No isolates secreted SEE, one produced SEA, and seven secreted SEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 21 publications
1
42
0
4
Order By: Relevance
“…The value of 65·04% of bovine isolates secreting TSST-1 and/or one or more enterotoxins is much greater than those of previous studies, where up to 52·0% of strains isolated from bovine mastitis produced enterotoxins (Lopes et al 1990;Kenney et al 1993;Matsunaga et al 1993;Aarestrup et al 1995;Ichikawa et al 1996;Bogni et al 1997). Moreover, these authors reported that enterotoxin C is the predominant type produced by bovine isolates of S. aureus, in contrast with human isolates, in which A is the main type.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The value of 65·04% of bovine isolates secreting TSST-1 and/or one or more enterotoxins is much greater than those of previous studies, where up to 52·0% of strains isolated from bovine mastitis produced enterotoxins (Lopes et al 1990;Kenney et al 1993;Matsunaga et al 1993;Aarestrup et al 1995;Ichikawa et al 1996;Bogni et al 1997). Moreover, these authors reported that enterotoxin C is the predominant type produced by bovine isolates of S. aureus, in contrast with human isolates, in which A is the main type.…”
Section: Discussionmentioning
confidence: 67%
“…According to Kenney et al (1993) and Aarestrup et al (1995) these results could be caused by differences between the strains and sources of S. aureus. In addition, Kenney et al (1993) suggested that differences might be a consequence of the concentration of proteins prior to immunodiffusion. In fact, some authors, such as Lopes et al (1990) (1997), have reported related a low level (4·5%) of S. aureus strains producing enterotoxins when detected by the OSP method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kenny et al (1993) of isolates recovered from cows in the USA showed that ca 20% of isolates produced TSST-1, generally in association with SEC and SED. In the present study, a similar proportion of isolates produced SEC and TSST-1 (16%) in detectable quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The strains were isolated from severe cases of bovine mastitis in a closed Frisian herd. Kenny et al 1993 found 28AE6% of enterotoxigenic Staph. aureus bovine isolates from mammary gland.…”
Section: Introductionmentioning
confidence: 99%